The Influence Of Sharia Financial Literacy On Students' Interest In Developing Sharia-Based Businesses At Muhammadiyah University Of Bima - Anya Sulistyaningsih; Ichwan P. Syamsudin; Muhammad Zia Ulhaq (JURNAL ECONOMINA, 2026)
This study aims to determine the effect of Islamic financial literacy on students’ interest in developing sharia-based businesses at Universitas Muhammadiyah Bima. This research used a quantitative approach with a survey method. Data were collected through questionnaires distributed to 50 student entrepreneurs. The data analysis techniques included validity test, reliability test, normality test, simple linear regression analysis, t-test, and coefficient of determination using SPSS software. The results showed that Islamic financial literacy has a positive and significant effect on students’ interest in developing sharia-based businesses. The better students understand Islamic financial principles, the higher their interest in running and developing businesses based on sharia principles.